2023
DOI: 10.3390/brainsci13081188
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Consequences of COVID-19: A Systematic Review of the Pandemic’s Impact on Neurology Training

Abstract: The COVID-19 pandemic had a significant impact on neurology training programs, leading to disruptions and changes that may have long-term implications for neurological education. The objective of this study was to investigate the impact of COVID-19 on neurological training programs, collecting available data relating to residents’ experience worldwide. We performed a systematic search of the literature published on PubMed from January 2020 to March 2023, including studies referring to quantitative analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Our results align with a recent European survey reporting that 41.9% of residents were confronted with suspended or delayed (63.4%) classes, and reduced time spent with neurological patients because of reassignments to clinical work in COVID‐19 units [54]. Moreover, a systematic review of the pandemic's impact on neurology residency revealed increased stress levels among trainees, which points to the need for psychological support [55]. A cutback in postgraduate training is not specific to neurology and was observed across other specialties.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results align with a recent European survey reporting that 41.9% of residents were confronted with suspended or delayed (63.4%) classes, and reduced time spent with neurological patients because of reassignments to clinical work in COVID‐19 units [54]. Moreover, a systematic review of the pandemic's impact on neurology residency revealed increased stress levels among trainees, which points to the need for psychological support [55]. A cutback in postgraduate training is not specific to neurology and was observed across other specialties.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, a systematic review of the pandemic's impact on neurology residency revealed increased stress levels among trainees, which points to the need for psychological support [55]. A cutback in postgraduate training is not specific to neurology and was observed across other specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Due to institutional adjustments and cost considerations, the public health committee did not collect data independently and develop an information system. Online communication also enables the transmission of more effective information ( 30 ). However, the public health committee also faces difficulties with data latency, data collection, and data exchange.…”
Section: Resultsmentioning
confidence: 99%
“…The impacts of the COVID-19 pandemic on the mental health and wellbeing of the healthcare workforce have been extensively highlighted [14][15][16][17][18]. A recent review on COVID-19 implications on neurology residents revealed the impact of the COVID-19 pandemic on experiencing psychological issues [19].…”
Section: Introductionmentioning
confidence: 99%